2021
DOI: 10.1101/2021.09.21.461213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-organized emergence of hyaline cartilage in hiPSC-derived multi-tissue organoids

Abstract: Despite holding great therapeutic potential, existing protocols for in vitro chondrogenesis and hyaline cartilage production from human induced pluripotent stem cells (hiPSC) are laborious and complex with unclear long-term consequences. Here, we developed a simple xeno- and feeder-free protocol for human hyaline cartilage production in vitro using hydrogel-cultured multi-tissue organoids (MTOs). We investigate gene regulatory networks during spontaneous hiPSC-MTO differentiation using RNA sequencing and bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Li and colleagues showed that long-term culturing of hiPSC-derived multi-tissue organoids (MTOs) in E8 medium results in a spontaneous emergence of hyaline cartilage tissues. Moreover, a transcriptome analysis indicated a strong association between the expression of chondrogenic markers in MTOs and fetal lower limb chondrocytes [ 52 ]. Another intriguing research demonstrated that subcutaneous implantation of iPSC-derived cartilage microtissues combined with pre-hypertrophic cartilage organoids in nude mice results in formation of both cartilaginous and bony regions [ 53 ].…”
Section: Main Textmentioning
confidence: 99%
“…Li and colleagues showed that long-term culturing of hiPSC-derived multi-tissue organoids (MTOs) in E8 medium results in a spontaneous emergence of hyaline cartilage tissues. Moreover, a transcriptome analysis indicated a strong association between the expression of chondrogenic markers in MTOs and fetal lower limb chondrocytes [ 52 ]. Another intriguing research demonstrated that subcutaneous implantation of iPSC-derived cartilage microtissues combined with pre-hypertrophic cartilage organoids in nude mice results in formation of both cartilaginous and bony regions [ 53 ].…”
Section: Main Textmentioning
confidence: 99%